A Study on Exploring the Innovation and Development of Audio-Visual Language Learning Media - Safriyani Novitri; M. Zaim; Harris Effendi Thahar; Diyah Ayu Risqiani (Scope : Journal of English Language Teaching, 2023)
The use of audio-visual components in educational materials has received a lot of attention due to the emphasis on efficient language learning methods. This study aims to investigate the innovation of audio-visual language learning media in the creation of cutting-edge audio-visual language learning materials and to analyze how it affects language learning and student engagement. The sample consisted of 25 students from second-year students majoring in English Department of Faculty and Education class B at Islamic University of Riau during the academic year 2022-2023. In order to gain a better understanding of the experiences, preferences, and suggestions for improvement of the learners, qualitative data was obtained through note-taking and observation. The results of this study help students understand the materials using audio-visual language learning and offers helpful suggestions for students, creators, and multimedia projects on how to successfully incorporate audio-visual components into language learning resources. The findings of this study could help motivate students and produce effective and interesting learning materials for language learners.